BANGUN APLIKASI IKLAN BERBASIS AUGMENTED REALITY PADA APARTMEN PARK VIEW CONDOMINIUM - Pani, Komang Bayu Yudhistira (Jurnal Kreativitas Mahasiswa Informatika, 2021)
This journal research about implementation Artificial Intelligence with Augmented Reality: (1) implementation process and Augmented Reality, (2) development model AR, (3) Artificial Intelligence application based AR, (4) Artificial Intelligence implementation with Augmented Reality. This journal is kind of development research. The development of a Augmented Reality application software with a comprehensive method of evaluation is: analysis, design, implementation and evaluation.